Australian trans and gender diverse people’s understandings of menopause: beyond cisgenderism, heterosexism, and binary-based gender in the current ‘menopause moment’ - Kerryn Drysdale; Yeşim Karasu; Lucy Watson (Health Promotion International, 2026)
Abstract In many high-income countries, including Australia, intensified political, social, and commercial visibility has been widely described as contributing to a contemporary ‘menopause moment’. This moment is propelled by the convergence of varied social, political, and economic drivers, but it is also unfolding within a context shaped by historically gendered assumptions about who experiences menopause and how it is experienced. While the current ‘menopause moment’ has raised awareness across a range of domains, there is also the risk of the amplification and normalisation of a particular type of person who experiences a particular type of menopause. Drawing on three focus groups conducted with 17 trans men and non-binary people with ovaries, this article attempts to intervene in the universalizing tendencies on which prevailing (and pervasive) discourses on menopause circulate. By paying close attention to how transgender and other gender diverse people defined, applied, and potentially resisted such discourses, we reveal how understandings of menopause among trans people were mediated both by their and others’ gender, and by the different contexts in which people experience hormonal change, including their experiences of gender affirmation. The contemporary discourses around menopause may be at a tipping point where paradoxically, in the wake of the heightened visibility of menopause, there is a risk of the increasing narrowness of the conversation. Now is the time to move menopause beyond cisgenderism, heterosexism, and binary-based gender so that trans people can be included in this contemporary ‘menopause moment’ as a matter of equitable health promotion.